Evaluation of Attendance Management Information System Employees at The Ministry of Religion Office - Nawi, Rusdin; Sahid, Muhammad (Manunggal Halim Jaya, 2024)
The purpose of writing this thesis is to describe and evaluate the employee attendance management information system implemented by the Jeneponto Regency Ministry of Religion Office and evaluate through PIECES analysis where the management information system is evaluated in terms of performance, information, economy, control, efficiency and services generated from the employee attendance management information system. The type of research used is qualitative research. The approach used in this research is a phenomenological approach where the purpose of this approach is to study in depth about the situation at the Jeneponto Regency Ministry of Religion Office. The results of this study show descriptions of the employee attendance management information system implemented at the Jeneponto Regency Ministry of Religion Office where the management information system used is a combination of several existing components such as software, hardware and networks used to organize core activities of managing employee attendance data starting from the process of recording employee attendance data using the Pusaka application. Attendance recapitulation reports, meal allowances and performance allowances can be seen by employees in the Absensi application. Management of employee attendance data as material for preparing reports for payment of employee benefits in the HRMS Presence application. The system has worked in accordance with the standard operating procedures (SOP) applied, but the process of recording employee attendance using the Pusaka application is also influenced by network conditions and servers. Analysis of the information produced is very fast and accurate, but in the output of the recapitulation of meal allowances there are differences in understanding between the manager and the output results of the system. From an economic point of view, the system used is free because it was developed by the Bureau of Personnel and the Bureau of Public Relations, Data and Information (HDI) of the Secretariat General of the Ministry of Religious Affairs of the Republic of Indonesia. To avoid the system from data corruption, the database is stored at the head office and limits access rights to several types of user accounts, but there is no feature of the system to prevent employee fraud when manipulating GPS when recording attendance using the Pusaka application. In this system, there are no activities that require wasted time for both humans and computers used, the information produced is also not excessive so that this system is far from the indicators that a system can be said to be inefficient. This system service is very helpful for employees, managers and management because in addition to being easy to use, the information generated is also immediately used as material in preparing reports for payment of meal allowances and employee performance allowances.